Hemophagocytic Lymphohistiocytosis Secondary to Disseminated Histoplasmosis in Rheumatologic Disease. (23rd January 2021) - Kusne, Yael; Christiansen, Michael; Conley, Christopher; Gea-Banacloche, Juan; Sen, Ayan
Abstract : Background . Hemophagocytic lymphohistiocytosis (HLH) was originally described in pediatric patients presenting with fever, hepatosplenomegaly, and blood cell abnormalities. Later, HLH was recognized to occur in adults, often associated with hematologic malignancies or serious infections. Conclusion . Patients presenting with HLH are critically ill, and rapid diagnosis is key. In adults, the search for the trigger must begin promptly as time to diagnosis effects survival. The underlying trigger in our patients was Histoplasma capsulatum infection, which is rare in the southwestern United States. Prompt diagnosis led to recovery in one patient, while the other did not survive.